Principal Leadership Strategy in Improving the Quality of Graduates Relevant to the Tourism Industry in Vocational High Schools (SMK) - Dahlia, Yunita; Asrin, Asrin; Setiadi, Dadi; Sudirman, Sudirman; Hakim, Mansur (Lafadz Jaya Publisher, 2024)
This research aims to describe the Principal's Leadership Strategy in Improving the Quality of Graduates Relevant to the Tourism Industry in Vocational Schools. This research was conducted using field research and used a descriptive-qualitative approach. Data collection techniques, observation, interviews, questionnaires, and documentation. Meanwhile, data analysis involves data collection, data reduction, data presentation, and drawing conclusions. Data validity checks use credibility, transferability, dependability, and confirmability tests as data validity checks. The results of the research show that the leadership strategy of vocational school principals in improving the quality of graduates relevant to the tourism industry is by (1) Increasing Competent Teacher Resources by appointing teachers whose academic qualifications are in accordance with the tourism department, facilitating tourism teachers to take competency training, improving performance tourism teachers in carrying out their main duties, increasing teacher welfare, and carrying out supervision of tourism teachers. (2). Implementation of learning carried out in vocational schools, namely adapting the school curriculum to the needs of DUDI